LATAR BELAKANG PENDIDIKAN ORANG TUA DAN KEDISIPLINAN TERHADAP PRESTASI BELAJAR - Muhlis Asianto; Heru Sriyono (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose to determine how much influence the parents' educational background and discipline  on the learning achievement of science at state junior high schools in East Jakarta. The research method used a survey method with correlation analysis, with the help of a questionnaire. Based on data analysis, it can be concluded that: (1) There is a significant influence of parents' educational background and discipline together on the social science learning achievement. This is evidenced by the acquisition of Sig = 0,000 < 0.05 and Fcount = 71,640. (2) There is a significant influence of parents' educational background on social science learning achievement. This is evidenced by the acquisition of Sig = 0.048 <0.05 and tcount = 2.011. (3) There is a significant influence of discipline on the achievement of social science learning achievements. This is evidenced by the acquisition of Sig = 0,000 <0.05 and tcount = 7.201.